2021
DOI: 10.1007/s12517-021-08468-3
|View full text |Cite
|
Sign up to set email alerts
|

Mapping tea plantations dynamics during 2000–2020 and monitoring biophysical attributes using multi-temporal satellite data in North Bengal (India)

Abstract: Tea is an important cash crop, and it becomes necessary to map the spatial distribution of tea plantations. The tea industry has been expanding rapidly in the Northeast region of India, and consequently, the area under tea plantations is changing rapidly which needs periodic monitoring. In this study, satellite data such as Landsat-5 Thematic Mapper (TM) and Sentinel-2A were deployed for tea plantation identification and to analyze the dynamics of tea extent in the North Bengal district during 2000 and 2020. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…From the RMSE calculation between observed and predicted data, the SAVI algorithm produces the smallest RMSE value. It means the SAVI index is the best algorithm to map tea plants and other vegetation types in this study (Parida & Kumari, 2021;Singh & Frazier, 2018).…”
Section: Data Processingmentioning
confidence: 90%
“…From the RMSE calculation between observed and predicted data, the SAVI algorithm produces the smallest RMSE value. It means the SAVI index is the best algorithm to map tea plants and other vegetation types in this study (Parida & Kumari, 2021;Singh & Frazier, 2018).…”
Section: Data Processingmentioning
confidence: 90%
“…The development and adoption of these technologies can contribute significantly to the overall prosperity of Assam's agricultural community. Numerous machine learning models are employed to delineate flood-prone areas and assess the health of tea leaves, facilitating proactive management [35][36][37]. Simultaneously, artificial intelligence systems forecast alternative crops based on soil and climate data, aiming to optimize land utilization and minimize associated risks [32][33][34] Not specified in the provided information [27] Not specified Review of evapotranspiration approaches and concepts.…”
Section: Machine Learning In Agricultural Growthmentioning
confidence: 99%
“…Green tea is regarded as the best among all tea varieties, having certain medical advantages in terms of antioxidant activity and a greater concentration of gallate content (Lou et al 2013). It is a non-alcoholic beverage consumed by over 66% of the world's population (Fu and Weng The influence of both international and domestic markets, as well as local factors, such as the expansion of tea plantations, were studied to determine the consequences of land use land cover (LULC) conversion over the last several decades (Nasir and Shamsuddoha 2011;Parida and Kumari 2021a). It was reported that between 1874 and 2010, the forest area dropped by almost 69.5%, while tea plantations expanded by 30.7% in the Himalaya Piedmont zone of India's West Bengal state (Prokop 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Because of their adequate geographic coverage with improving spatial resolution, satellite images are employed for tea plantations mapping and monitoring (e.g., Landsat series, IRS series, SPOT series, and Sentinel). Tea plantations in north Bengal regions in West Bengal (India) were detected and analysed using Sentinel-2 Multi Spectral Instrument (MSI) and Landsat-5 Thematic Mapper (TM) sensors (Parida and Kumari 2021a). High spatiotemporal multispectral data were also employed to study the tea plantation's phenological features in northern Zhejiang from April to May 2018 (Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%